Existence of Almost Periodic Solutions for Impulsive Neutral Functional Differential Equations - Junwei Liu; Chuanyi Zhang (Abstract and Applied Analysis)
The existence of piecewise almost periodic solutions for impulsive neutral functional differential equations in Banach space is investigated. Our results are based on Krasnoselskii’s fixed-point theorem combined with an exponentially stable strongly continuous operator semigroup. An example is given to illustrate the theory.